Use of Metformin to Prolong Gestation in Preterm Preeclampsia. Issue 3 (24th September 2022) - Cluver, C.A.; Hiscock, R.; Decloedt, E.H.; Hall, D.R.; Schell, S.; Mol, B.W.; Brownfoot, F.; Kaitu'u-Lino, T.J.; Walker, S.P.; Tong, S.
Abstract : ( BMJ . 2021;374:n2103) Preterm preeclampsia affects 10% of all women with preeclampsia worldwide. Although preeclampsia prevention is attempted with therapies including low-dose aspirin, there are no current treatments for preeclampsia once diagnosed other than delivery. Preterm preeclampsia causes increased risk for both maternal and neonatal morbidity and mortality, especially in developing areas without adequate obstetric or NICU care.